PERBANDINGAN KANDUNGAN LOGAM BERAT (Cu, Fe dan Zn) PADA AIR SUNGAI SIAK SEBELUM DAN SESUDAH PROSES PENJERNIHAN - Rutmayanti Pandiangan; Sugianto '; Usman Malik (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
Comparison of heavy metal (Cu, Fe and Zn) content of Siak river water between before and after purification process has been done using an experimental method. The processstarted by taking sample of the Siak River water at a distance of 1 meter from waste sewage system of rubber manufacturing industry PT.RICRY Pekanbaru. Concentration of pre-filtered samples was measured by atomic absorption spectrophotometer (AAS), then each sample was filtered five times. The result of pre-filtered samples characterized by (AAS) of Cu, Fe and Zn were 0.3809 ppm, 0.0051 ppm, and -0.0012 ppm. The absorption percentage of samples characterized by (AAS) for Fe, Zn and Cu were 12,02 %, 33,33 % and 72,54 %, respetively (type I) and 33,15 %, 2,70 % and 80,39 % respetively for type II. Based on the obtained data, it was concluded that the purity instrument of type I was better than type II for water treatment.